Biochemical propensity mapping for structural and functional anatomy of importin α IBB domain. (11th January 2022) - Jibiki, Kazuya; Liu, Mo‐yan; Lei, Chao‐sen; Kodama, Takashi S.; Kojima, Chojiro; Fujiwara, Toshimichi; Yasuhara, Noriko
Abstract: Importin α has been described as a nuclear protein transport receptor that enables proteins synthesized in the cytoplasm to translocate into the nucleus. Besides its function in nuclear transport, an increasing number of studies have examined its non‐nuclear transport functions. In both nuclear transport and non‐nuclear transport, a functional domain called the IBB domain (importin β binding domain) plays a key role in regulating importin α behavior, and is a common interacting domain for multiple binding partners. However, it is not yet fully understood how the IBB domain interacts with multiple binding partners, which leads to the switching of importin α function. In this study, we have distinguished the location and propensities of amino acids important for each function of the importin α IBB domain by mapping the biochemical/physicochemical propensities of evolutionarily conserved amino acids of the IBB domain onto the structure associated with each function. We found important residues that are universally conserved for IBB functions across species and family members, in addition to those previously known, as well as residues that are presumed to be responsible for the differences in complex‐forming ability among family members and for functional switching. Abstract : In this study, we have distinguished the location and propensities of amino acids important for each function of the importin α IBB domain by mapping the biochemical/physicochemical propensities of evolutionarily conserved amino acids of the IBB domain onto the structure associated with each function. We found important residues that are universally conserved for IBB functions across species and family members, in addition to those previously known, as well as residues that are presumed to be responsible for the differences in complex‐forming ability among family members and for functional switching.